2019
DOI: 10.1037/pas0000663
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of virtual reality for psychological testing.

Abstract: Virtual reality (VR) is rapidly becoming an inexpensive, mainstream technology. VR technology is superambulatory as it allows participants to be examined under standardized environments and tests anywhere. In addition, it can test participants in different virtual spaces, including environments that are unsafe, inaccessible, costly or difficult to set up, or even nonexistent. We summarize the benefits and potential problems of VR technology, but we also move beyond theoretical approaches and present a customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…Our study was limited by our choice of a healthy, predominantly White and Asian sampling frame that had ready access to outdoor nature. The limited age range (18-27) represents a population likely comfortable with and inclined toward the use of VR (Roberts et al, 2019). While we did not observe differences in affective responses between participants with experience in VR and participants without such experience, populations less familiar or accepting of electronic technology may be less likely to benefit from a sensory-rich simulated environment like VR without adverse events, safety concerns, or poor adherence rates (Miller et al, 2014).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our study was limited by our choice of a healthy, predominantly White and Asian sampling frame that had ready access to outdoor nature. The limited age range (18-27) represents a population likely comfortable with and inclined toward the use of VR (Roberts et al, 2019). While we did not observe differences in affective responses between participants with experience in VR and participants without such experience, populations less familiar or accepting of electronic technology may be less likely to benefit from a sensory-rich simulated environment like VR without adverse events, safety concerns, or poor adherence rates (Miller et al, 2014).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…VR creates a sense of presence which is an integral component for a system that relies on automatic physiological responses. Roberts et al (2019) suggest that VR tests are comparable to real-life testing, demonstrating the validity of this medium for psychological assessment studies. Additional studies indicate the suitability of using VR for simulating the sense of presence in a corresponding real physical space (Kuliga et al 2015;Maghool et al 2018, Yeom et al 2019.…”
Section: )mentioning
confidence: 71%
“…The task has already been used in a VR (Roberts et al, 2019) in which authors proposed a proof of concept by comparing the performances in VR environment and the usual laboratory situation conditions. They showed that performances were largely equivalent in both situations.…”
Section: A Flankers Task In Virtual Realitymentioning
confidence: 99%